2022
DOI: 10.1002/tox.23668
|View full text |Cite
|
Sign up to set email alerts
|

CircRPPH1 promotes the stemness of gastric cancer cells by targeting miR‐375/SLC7A11 axis

Abstract: This study mainly focuses on revealing the role of circRPPH1 in gastric cancer cell stemness. In vitro and in vivo experiments were performed to evaluate the effects of circRPPH1 on gastric cancer cell stemness. Luciferase reporter and RIP assays were implemented to reveal the underlying mechanisms. MiR‐375 directly bound to circRPPH1 in gastric cancer cells. And circRPPH1 acted as an miR‐375 sponge to positively regulate SLC7A11 expression, which has been confirmed to be the direct target of miR‐375 in gastri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Existing study has confirmed that GC patients with unbalanced expression of SLC7A11-AS1/xCT axis had a poor prognosis and relatively poor response to chemotherapy [ 19 ]. SLC7A11 also acts as an epigenetic co-factor to interfere with the stemness of GC cells [ 20 ]. RAC1 (Ras-related C3 botulinum toxin substrate 1) is a small GTPase, the upregulation of which activates disulfidptosis [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Existing study has confirmed that GC patients with unbalanced expression of SLC7A11-AS1/xCT axis had a poor prognosis and relatively poor response to chemotherapy [ 19 ]. SLC7A11 also acts as an epigenetic co-factor to interfere with the stemness of GC cells [ 20 ]. RAC1 (Ras-related C3 botulinum toxin substrate 1) is a small GTPase, the upregulation of which activates disulfidptosis [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has revealed that in GC cells, miR-375 can directly interact with circRPPH1. The latter is highly expressed in GC cells and relies on the miR-375/SLC7A11 axis to enhance the stemness of GC cells ( Liu et al, 2023 ). Gao et al found that circ0008035 acts as a sponge for miR-302a, thereby increasing the expression of downstream protein target E2F7 in GC cells.…”
Section: The Regulatory Mechanisms Of Ferroptosis In Gc Cellsmentioning
confidence: 99%
“…SLC7A11 and GPX4, two important ferroptosis suppressors and markers, are targets not only for small molecules as ferroptosis inducers but also for a large group of ncRNAs regulating ferroptosis. MiR-409-3p, miR-515-5p, miR-375, miR-1261, miR-489-3p, miR-128-3p, miR-545-3p, miR-5096, miR-520d-5p, miR-125b-5p, miR-34c-3p, miR-143-3p, miR-26a-5p, miR-27b-3p, miR-587, miR-194-5p, miR-27a-3p, miR-520a-5p, miR-1184, miR-6077, miR-485-5p, miR-25-3p, miR-513a-3p, miR-206, and miR-431 have been reported to target and repress SLC7A11 to promote ferroptosis in cervical cancer [233], gastric cancer [148,234,235], liver cancer [236], prostate cancer [146], thyroid cancer [237], breast cancer [238], oral squamous cell carcinoma [239][240][241], kidney cancer [242,243], ovarian cancer [244,245], lung cancer [147,[246][247][248][249], prostate cancer [250], esophageal squamous cell carcinoma [251], osteosarcoma [252], and colorectal cancer [253]. MiR-378a-3p, miR-27a, miR-144-3p, and exosomal miR-26b-5p from patients with acute myocardial infarction target and reduce SLC7A11 expression to induce ferroptosis in the IRI of the kidney [254], brain [255], and heart [256,257].…”
Section: Ncrnas Regulating Ferroptosis Through Antioxidant Defensementioning
confidence: 99%